Assessment of transport network vehicle services based on social aspects of sustainable transport in Metro Manila - Naral, Mathew A.; Villarin, Christian F.; Regidor, Jose Regin F. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Transport Network Vehicle Services (TNVS) such as Uber and Grab have risen to popularity recently in Southeast Asia especially in the Philippines. Adoption and implementation of these services impose problems for transportation engineers and urban planners. This paper aimed to assess the services in the context of social aspects of sustainable transport as defined in this research. Criteria such as equity, security and safety were set by the researchers for the analysis of the results from the survey instruments. The scope of the study is only within Metro Manila and is limited to Uber/Grab passenger. Survey forms were disseminated online through social media for better reach. Questionnaires gathered the demographics of respondents, travel practices, driver and vehicle evaluation, and the overall assessment quality of these services. Correlation between certain parameters includes monthly income, travel cost and time. Findings show that accessibility was the major reason of people shifting to Uber/Grab. This study determined if the emergence of TNVS has brought improvement in terms of social aspects of sustainable transport.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Transportation -- Social aspects; Transportation -- Philippines -- Manila; Transportation network vehicle services (TNVS).